2007
DOI: 10.1055/s-2007-981502
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction with Rectus Abdominis Myocutaneous Flap for Total Glossectomy with Laryngectomy

Abstract: From October 1999 to July 2005, defects after total glossectomy with laryngectomy (TGL) for cancer of the tongue or middle pharynx were reconstructed with rectus abdominis myocutaneous (RAMC) flaps in nine patients. The skin flaps were designed larger in width than the original defect to create a funnel-shaped oropharynx and prevent stricture. Six patients had uneventful postoperative courses and began to eat perorally 8 to 15 days postoperatively. One patient suffered flap necrosis due to arterial thrombosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
(26 reference statements)
0
14
1
Order By: Relevance
“…To avoid this complication, Okazaki et al 17 suggested widening the part of the flap corresponding to the oral floor, de-epithelializing this, and inserting it just below the anterior suture line. In this way, a portion of subcutaneous tissue is placed between the skin and the mucosa and it can be sutured to the mandibular bone.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid this complication, Okazaki et al 17 suggested widening the part of the flap corresponding to the oral floor, de-epithelializing this, and inserting it just below the anterior suture line. In this way, a portion of subcutaneous tissue is placed between the skin and the mucosa and it can be sutured to the mandibular bone.…”
Section: Discussionmentioning
confidence: 99%
“…28 The flap, which needs to be about 10 cm wide, can be used to line the floor of the mouth and used as a patch for partial pharyngectomy defects or tubed to reconstruct circumferential pharyngeal defects. In patients with adequate skin laxity, the donor-site defect can be closed primarily.…”
Section: Total Glossectomy With Laryngectomymentioning
confidence: 99%
“…Donor site morbidity should be given particular attention in pediatric cases due to its impact on future growth. There are various flap options for tongue reconstruction, such as the radial forearm free flap (RFFF), anterolateral thigh (ALT) free flap, transverse gracilis myocutaneous (TMG) free flap, and rectus abdominis myocutaneous (RAMC) free flap . RFFF and ALT free flaps are able to achieve ideal tongue reconstruction; however, they are associated with unacceptable donor site scar formation, especially in young female patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are various flap options for tongue reconstruction, such as the radial forearm free flap (RFFF), anterolateral thigh (ALT) free flap, transverse gracilis myocutaneous (TMG) free flap, and rectus abdominis myocutaneous (RAMC) free flap. [4][5][6][7][8][9] RFFF and ALT free flaps are able to achieve ideal tongue reconstruction; however, they are associated with unacceptable donor site scar formation, especially in young female patients. In addition, ALT flaps obtained from this age group often do not contain sufficient adipose tissue to allow bulky tongue reconstruction.…”
Section: Discussionmentioning
confidence: 99%